2013
DOI: 10.1186/2191-219x-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing statistical parametric mapping analysis of 18F-FDG PET in children

Abstract: BackgroundStatistical parametric mapping (SPM) procedure is an objective tool to analyze 18F-fluoro-2-deoxy-d-glucose-positron-emission tomography (FDG-PET) images and a useful complement to visual analysis. However, SPM requires a comparison to control data set that cannot be obtained in healthy children for ethical reasons. Using adults as controls showed some limitations. The purpose of the present study was to generate and validate a group of pseudo-normal children as a control group for FDG-PET studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 38 publications
(63 reference statements)
4
80
1
Order By: Relevance
“…We have shown that lobar accuracy of detection of the SOZ is similar to previously reported lobar accuracies in older pediatric and young adult groups [Lee et al, 2005; Kumar et al, 2010; Archambaud et al, 2013; vant’ Klooster et al, 2014]. In addition, by directly measuring the nearest Euclidean distance between ECoG-defined SOZ and SPM metabolic clusters on the actual 3D brain surface of individual patients, we found that 1) large portions of the hypometabolic abnormalities are located outside the SOZ, often at 30mm distance or beyond; 2) the hypometabolic abnormality provided slightly higher sensitivity to overlap focal SOZ than widespread SOZ; 3) hypermetabolic clusters were detected in 2/3 of the cases and were often associated with interictal epileptiform activity during FDG uptake; however, these hypermetabolic abnormalities were also observed mostly outside the ECoG-defined SOZ or ‘interictal spike zone’.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We have shown that lobar accuracy of detection of the SOZ is similar to previously reported lobar accuracies in older pediatric and young adult groups [Lee et al, 2005; Kumar et al, 2010; Archambaud et al, 2013; vant’ Klooster et al, 2014]. In addition, by directly measuring the nearest Euclidean distance between ECoG-defined SOZ and SPM metabolic clusters on the actual 3D brain surface of individual patients, we found that 1) large portions of the hypometabolic abnormalities are located outside the SOZ, often at 30mm distance or beyond; 2) the hypometabolic abnormality provided slightly higher sensitivity to overlap focal SOZ than widespread SOZ; 3) hypermetabolic clusters were detected in 2/3 of the cases and were often associated with interictal epileptiform activity during FDG uptake; however, these hypermetabolic abnormalities were also observed mostly outside the ECoG-defined SOZ or ‘interictal spike zone’.…”
Section: Discussionsupporting
confidence: 89%
“…Although several previous studies utilized voxel-wise SPM analysis to objectively detect metabolic abnormalities in children with intractable epilepsy, none of those studies have reported how closely and accurately the SPM-defined cluster can detect ECoG-defined SOZ. Specifically, to define PET accuracy, the partial or total overlap of the hypometabolic region with the SOZ had been determined on either lobar basis or gyral level in previous studies [Kumar et al, 2010; Archambaud et al, 2013; vant’ Klooster et al, 2014]. This approximation of spatial correspondence inevitably resulted in variable performance of SPM analysis across the literature (e.g., sensitivity/specificity= 0.86/0.77 [Kumar et al, 2010], 0.79/0.97 [Archambaud et al, 2013], 0.35/0.90 [vant’ Klooster et al, 2014]).…”
Section: Discussionmentioning
confidence: 99%
“…Cluster significant thresholds (extend threshold) were set at 50 contiguous voxels (Archambaud et al, 2013). Based on the results of previous studies (Dumas de la Roque et al, 2005, Gross, 2011), we selected only FA decrease and MD increase for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…However, the visual assessment of 18 F-FDG PET images in the clinical application is subjective and relies on the experience and knowledge of the readers (23). Therefore, it is inevitable that the interpretation of a single image by visual assessment is variable among different observers, and subtle metabolic abnormalities of epilepsy might not be identified easily.…”
Section: Discussionmentioning
confidence: 99%